2016
DOI: 10.1016/j.scr.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological blockage of fibro/adipogenic progenitor expansion and suppression of regenerative fibrogenesis is associated with impaired skeletal muscle regeneration

Abstract: Acute skeletal muscle injury triggers an expansion of fibro/adipogenic progenitors (FAPs) and a transient stage of fibrogenesis characterized by extracellular matrix deposition. While the perpetuation of such phase can lead to permanent tissue scarring, the consequences of its suppression remain to be studied. Using a model of acute muscle damage we were able to determine that pharmacological inhibition of FAP expansion by Nilotinib, a tyrosine kinase inhibitor with potent antifibrotic activity, exerts a detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 29 publications
6
124
1
Order By: Relevance
“…FAP cells are then eliminated by apoptosis that is driven by TNF released from M1-biased macrophages 31 . However, during their few days of pro-fibrotic activity, they modulate the developmental programme of MPCs to influence the course of muscle regeneration 31,88 .…”
Section: Immune Cell Interactions With Fap Cells In Musclementioning
confidence: 99%
“…FAP cells are then eliminated by apoptosis that is driven by TNF released from M1-biased macrophages 31 . However, during their few days of pro-fibrotic activity, they modulate the developmental programme of MPCs to influence the course of muscle regeneration 31,88 .…”
Section: Immune Cell Interactions With Fap Cells In Musclementioning
confidence: 99%
“…Following acute injury, FAPs activate and amplify, some are eliminated by apoptosis induced by pro-inflammatory cytokines such as IL4 (Joe et al, 2010). Coculture experiments demonstrated that FAPs represent a transient source of pro-differentiation factors for driving proliferating myoblast differentiation and fusion; and it has been shown that pharmacological inhibition of FAP proliferation and differentiation, or diphtheria toxin ablation of these cells results in impaired muscle regeneration (Fiore et al, 2016;Murphy et al, 2011). On the other hand, during chronic degeneration/regeneration, FAPs are the main source of fibrosis, and in dystrophic mice, the combination of a pro-and anti-inflammatory secretome (Villalta et al, 2009) maintains FAPs survival and differentiation into matrix-producing cells similar to fibroblasts (Lemos et al, 2015).…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerativementioning
confidence: 99%
“…Here we show that PDGFRα signaling regulates a population of muscle-resident fibro/adipogenic progenitors (FAPs) that play a supportive role in muscle regeneration but may also cause fibrosis when aberrantly regulated. 1013 We found that FAPs produce multiple transcriptional variants of PDGFRα with different polyadenylation sites, including an intronic variant that codes for a protein isoform containing a truncated kinase domain. This variant, upregulated during regeneration, acts as a decoy to inhibit PDGF signaling and to prevent FAP over-activation.…”
mentioning
confidence: 99%